الصكوك الإسلامية والتعامل بها فى السوق المالي الماليزي : دراسة تحليلية نقدية - عبد الله، فيصل محمود (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The issue of Sukuk is one of the contemporary issues in the field of Islamic economy, especially in the area of financial institutions and markets. It stands as an alternative to conventional bonds, which Islamic economic thought is attempting to close its doors in dealing with it in the markets of the Muslim world. The study sheds light on the mechanism of the Sukuk, and how they are managed in the Malaysian financial market. Meanwhile, it also discusses the theoretical part of the securitization process, its concept, purposes, benefits, steps, elements, and the fundamental differences between the processes of Islamic securitization, and conventional securitization. It also covers issues pertaining to the essence of Islamic bonds (Sukuk), their features, the differences between them and traditional securities (stocks and bonds), and its legal ruling in the circulation, and amortization, in addition to the guarantees provided to bondholders. However, regarding its practical aspect, the study highlights how Sukuk (Murabaha, istisna'a, Mudharabah, and Musharakah) are applied in the Malaysian financial market. The study concludes that the Sukuk that operate in the Malaysian financial Market involve violation of the Islamic legal ruling, due to non-observance of the Islamic rules pertaining to Sukuk and Islamic rulings for the contract on which bases Sukuk are issued. That is why many Malaysians believe that the Islamic investment is not much different from the traditional investment which has taken the system of borrowing and lending for an interest-base as the basis of its transactions. However, the study was based on multiple research methods, such as the Inductive, Comparative, Analytical, Critical, and Applied methods, according to the needs of the research.